Strategi Pengembangan Produk Jajanan Tradisional Klepon Di Klepon Legend Gianyar - Wardana, Gede Wahyu; Yuarini, Dewa Ayu Anom; Sadyasmara , Cok Anom Bayu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
In 2022-2023 Klepon Legend experienced a 15% decrease in sales. Based on interviews with business owners, one of the factors affecting this decline in sales is because there are competitors who offer similar products from Klepon Gianyar 1980 and also Klepon Gianyar Dayu Niang Eka. The purpose of this study is to determine the quality attributes of klepon products, determine the level of importance and consumer satisfaction, and formulate product development strategies at Klepon Legend. The analysis method used in the research is Quality Function Deployment (QFD) and the variables used are the quality attributes of klepon products, namely color, aroma, taste, texture, shape, size, portion. Based on QFD analysis, the product quality attribute with the highest importance value is the flavor attribute for attributes that get the highest satisfaction value is the menu portion and size. The product development strategy that can be recommended based on the characteristics of the respondents is that Klepon Legend can innovate klepon dough by adding flavor and aroma variants such as matcha, taro, red velvet and chocolate.